Methodology for the evaluation of graduation attributes: case of the School of Civil Engineering, University of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2023)
The measurement of graduation attributes is a common evaluation criterion of the accrediting agencies of engineering programs. This work evaluates the experience of the School of Civil Engineering, University of Costa Rica, in order to synthesize the pilot evaluation methodology created that measures three graduation attributes: basic knowledge, research and use of engineering tools. The suitability of the use of rubrics as an evaluation instrument is assessed, through a quantitative approach. The sample was 347 students during 2017. The results showed that the rubrics require work to prepare and apply, and may not be the most suitable option to evaluating hard attributes. The methodology has great replication potential, although limitations were identified to standardize it to other attributes.
Keywords: Accreditation, Civil Engineering; Higher education; Education program evaluation